Stripped sour water treatment by advanced oxidation processes - Guimarães,José R. (2012)
This study assessed the application of photolysis (UV), peroxidation (H2O2), peroxidation combined with ultraviolet light (UV/H2O2), Fenton’s reagent (H2O2/Fe(II)) and photo-Fenton (H2O2/Fe(II)/UV) processes in the treatment of stripped sour water from the Petrobras Replan Oil Refinery in Paulínia City, São Paulo State, Brazil. To evaluate the efficiency of the process, the concentration of dissolved organic carbon (DOC) was monitored throughout the reaction period. Among the evaluated processes, peroxidation combined by ultraviolet radiation showed the best potential for its application in the stripped sour water treatment.